THE USE OF THEORY OF PLANNED BEHAVIOR (TPB) FOR SHARIA INVESTMENT INTENTIONS: COMPARISON BETWEEN SUKUK AND SHARIA STOCKS - Ilham Rhamadona; Andini Tanjung; Fauzan Abdillah (International Conference on Business Management and Accounting, 2022)
The purpose of this study is to test the theory of planned behavior for sharia investment intentions. Data were collected using a questionnaire distributed online. more than 100 respondents participated in both studies. The collected data was then analyzed using SPSS software. The findings of this study are that there is a positive and significant influence between subjective attitudes and norms with the intention to invest in Sukuk and Sharia Stocks. but unfortunately, the perceived behavioral control variable has a positive but not significant effect. The implication of the findings of this study is that parties with an interest in increasing public participation in sharia investing can design the right program to achieve its goals.